2012
DOI: 10.1152/physiolgenomics.00140.2011
|View full text |Cite
|
Sign up to set email alerts
|

Differential genomic changes caused by cholesterol- and PUFA-rich diets in regenerated porcine coronary endothelial cells

Abstract: Endothelial regeneration and dyslipidemia impair endothelium-dependent relaxation, while supplementation with fish oil (FO) prevents it. The genomic impact of different diets was compared in primary cultures derived from native and regenerated endothelial cells. Pigs were fed with high-cholesterol (CHL) or FO-rich diet. Partial in vivo removal of endothelium was performed to induce endothelial regeneration. Native and regenerated cells were harvested, cultured, and prepared for genomic (microarray experiments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In P4 cells, the ratio of phosphorylated SIRT1 (p-SIRT1) to total SIRT1 (t-SIRT1) was augmented Ͼ9-fold compared with that in P1 cells. The p-SIRT1 levels in regenerated endothelial cells collected from porcine aortas 4 weeks after balloon denudation injury 29 were also elevated compared with native cells ( Figure 1A, right). The association of p-SIRT1 with cellular senescence was further confirmed in PAECs treated with hypercholesterolemic serum collected from ApoE Ϫ/Ϫ mice, H 2 O 2 , or low-density lipoprotein cholesterol ( Figure 1B and 1C).…”
Section: Endothelial Senescence Is Associated With Increased Phosphormentioning
confidence: 93%
See 1 more Smart Citation
“…In P4 cells, the ratio of phosphorylated SIRT1 (p-SIRT1) to total SIRT1 (t-SIRT1) was augmented Ͼ9-fold compared with that in P1 cells. The p-SIRT1 levels in regenerated endothelial cells collected from porcine aortas 4 weeks after balloon denudation injury 29 were also elevated compared with native cells ( Figure 1A, right). The association of p-SIRT1 with cellular senescence was further confirmed in PAECs treated with hypercholesterolemic serum collected from ApoE Ϫ/Ϫ mice, H 2 O 2 , or low-density lipoprotein cholesterol ( Figure 1B and 1C).…”
Section: Endothelial Senescence Is Associated With Increased Phosphormentioning
confidence: 93%
“…Native and regenerated endothelial cells were collected from pigs subjected to coronary angioplasty as described. [27][28][29] …”
Section: Isolation and Culture Of Primary Porcine Aortic Endothelial mentioning
confidence: 99%
“…This experiment identified 5 genes with atheroprotective functions that were downregulated in the regenerated cells while another 9 pro-atherogenic genes were upregulated. 19 Information derived from this and other deep phenotyping studies could be used further to identify genes or proteins that could be targeted for genetic manipulation to restore normal endothelial function. In addition, profiling studies should take into account the effects of antiproliferative drugs eluted from stents on the endothelium.…”
mentioning
confidence: 99%
“…The reason why this proposal is not too surprising, at least to us, is that a few years ago, we studied (with microarrays) the genomic profile of primary cell cultures of native and regenerated (after balloon angioplasty) porcine coronary endothelial cells from the same hearts [2]. More recently, we have repeated those studies in pigs fed chronically with diets rich in either cholesterol or x 3 -unsaturated fatty acids [3]. As always in such scientific fishing expeditions, a large number of genes were either up-or down-regulated.…”
mentioning
confidence: 99%
“…However, regenerated endothelial cells expressed the mRNA for two genes that were not found in native cell cultures, MMP-7 and FABP4 [2]. The over-expression persisted in regenerated endothelial cells irrespective of the diet to which the donor animals were subjected [3]. We concluded that the over-expressions of these two genes, MMP7 and FABP4, are major inducing factors of endothelial dysfunction.…”
mentioning
confidence: 99%